Two suppletive adjectives in Megleno-Romanian - Maiden, M (John Benjamins Publishing Company, 2014)
This study involves the existence in Megleno-Romanian dialects of a lexically suppletive distinction between singular and plural forms of the adjectives meaning ‘small’ and ‘big’. The phenomenon has gone largely unnoticed both by comparative Romance linguists and by morphological theorists yet it is both typologically surprising and theoretically significant. Analysis of a remarkably similar phenomenon in mainland Scandinavian languages led Börjars and Vincent (2011) to propose a considerably attenuated version of Maiden’s claim (2004) that lexical synonymy can drive the diachronic emergence of suppletion. My close investigation of the the source of the suppletion in Megleno-Romanian, and consideration of the Scandinavian facts in the light of the Megleno-Romanian data, will show that in fact the emergence of suppletion in just these adjectives constitutes excellent evidence for the claim that lexical synonymy favours suppletion.